Cliometrics and the future of economic history - Claude Diebolt; Michael J. Haupert (Essays in Economic & Business History (EEBH), 2022)
We give an overview of the origins of the Cliometric revolution, its place within the larger economic history discipline, and what we see as the future of cliometrics and economic history, not as separate disciplines, but as complementary approaches to thestudy of economic growth in the long run.
Keywords: N01; 330; cliometrics; economic history